Controversies in the Treatment of Classical Hodgkin Lymphoma. Issue 5 (October 2018) - Eichenauer, Dennis A.; André, Marc; Johnson, Peter; Fossa, Alexander; Casasnovas, Olivier; Engert, Andreas
Abstract : Abstract: Hodgkin lymphoma (HL) is a B-cell-derived malignancy that mostly affects young adults. Pathologically, HL is divided into classical HL (cHL) and the rare entity of nodular lymphocyte-predominant HL. Classical HL is characterized by few malignant cells termed Hodgkin and Reed–Sternberg cells embedded in an inflammatory background. The treatment of cHL has consistently improved over the last decades so that current standard approaches result in long-term remission rates in excess of 80%. However, potentially lethal therapy-related late complications affect an increasing number of survivors. For this reason, issues regarding the optimal treatment of cHL patients are still fiercely debated. Questions under discussion include how treatment can be guided by interim positron emission tomography, the best initial treatment for advanced-stage disease and the use of targeted drugs such as the antibody–drug conjugate brentuximab vedotin and the anti-PD-1 antibodies nivolumab and pembrolizumab. The identification of patients who should undergo allogeneic stem cell transplantation is another unsolved issue. The present article highlights the most relevant clinical trials and addresses controversial open questions in the treatment of cHL.